Book Review of State-Business Relations and Economic Development in Africa and India Edited by Kunal Sen - Sisombat, Lili (Taylor and Francis, 2014)
From a practitioner point of view, State-Business Relations and Economic Development in Africa and India edited by Professor Kunal Sen is an immensely useful book. It presents a variety of case studies in Africa and India looking at the effects of state-business relations (SBRs) on economic performance both at the macro and micro level. The work derives from empirical research in sub-Saharan Africa and South Asia and asks three questions: first, what characterizes effective SBRs and how have they evolved over time; second, what are the effects of effective SBRs on economic performance at the micro, meso and macro level; and, third, how do effective SBRs emerge? These are crucial questions for practitioners who are working on the reform process and are building coalitions to address critical regulatory issues.